Designing a Model of Selection and Assessment of Hospital Outsourcing Services Based on Approach Hierarchical Possess(AHP)in Hospitals - Rouhangiz Asadi; Masoud Etemadian; Pejman Shadpour; Fatemeh Semnani (Tehran University of Medical Sciences, 2018)
Background: In recent years, Hashemi Nejad Hospital was outsourced or insourced some of their services to private sector or will have decision to do it. Selection and assessment of suppliers in outsourcing of hospital services is a critical issue. In this study, selecting and evaluating suppliers for outsourcing services in hospitals was evaluated. Materials and Methods: In order to achieve the goal, evaluating and selecting outsourcing service providers with studies and using opinion of the experts and medical experts, consisting of hospital manager, quality manager, HR managers, officials outsourced parts and other experts in this respect which includes 14 criteria. Identified criteria were clustered in three areas of service features, characteristics and criteria for communications suppliers in the supply chain; supplier selection problem is the problem multi-criteria decision. So, criteria were ranked and weighted using the Expert choice 11 software and AHP. Results: Based on the study results, sub-criteria of the quality of service, management systems, customer care, and information security had greatest impact on the selection of suppliers and sub-criteria, geographic location, flexibility and problem solving had the lowest priority. Conclusion: C supplier had the highest priority according to the communication criteria and A supplier had the highest priority according to two other criteria. In total, the supplier A had the first priority, supplier B had the second priority and supplier C had the third priority.